The ZnO-CuO Nanoporous Composite Synthesized using Gum Arabic (Acacia senegalensis) as an Emerging Nanolarvicide for Culex quinquefasciatus Larvae Management - Shehu, Zaccheus; Abba, Ezra; Emmanuel, Blessing (Iraqi Journal of Science, 2022)
Culex quinquefasciatus is an intermediate host of several human pathogens and serve as a vector of filariasis worldwide. Recently, there are increasing efforts to develop new and effective nanoparticles to control mosquito vectors. The green synthesis of ZnO-CuO nanoporous composite using Gum Arabic (Acacia senegalensis) was successfully carried out with Gum Arabic and the composite was characterized by UV-Visible, FTIR, and SEM/EDX techniques. Three different larval instars (1st, 2nd, and 3rd) of Culex quinquefasciatus were exposed to various concentrations (10, 20, 25 mg/l) of the ZnO-CuO nanocomposite for 24 h. The LC50 values for the 1st, 2nd, and 3rd instars were found to be 4.702, 5.459, and 5.459, respectively, while the LC90 values were 22.923, 33.922, and 33.922, respectively. The correlation coefficient values for the three instars were found to be 0.982, 0.941, and 0.941, respectively, and these indicate concentration-dependent larvicidal activity. The novel ZnO-CuO nanoporous composite could serve as a new nanolarvicide against the filariasis-transmitting vector.